1990
DOI: 10.1111/myc.1990.33.6.283
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplenic candidosis ‐ a late manifestation of Candida septicemia

Abstract: Summary Hepatolienal candidosis was diagnosed in 27 patients suffering from malignant hematologic disorders. All patients had received intensive cytostatic chemotherapy and developed septic, antibiotic‐resistant temperatures during severe treatment‐induced neutropenia. During neutropenia hepatic and splenic foci were not identified by imaging procedures. Foci were poorly defined histologically. Blastospores and pseudomycelia were seen in non‐reactive tissue and within necrotic areas in the liver, spleen, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In addition, our patients were able to leave the hospital after 1 week. In contrast, in historical studies, the time to resolution of fever has exceeded 4 weeks (range, 9-196 days) [4,6,17]; nausea and vomiting has taken 6-8 weeks to resolve [18], and increased levels of liver enzymes persisted for a mean of 4.4 months (range, 1 week to 12 months) [19]. Of note, in our study, CDCrelated radiological abnormalities disappeared within a mean of 106 days (range, 30-210 days)-a result not significantly different from that of historical series (mean, 100 days; range, 28-390 days) [18], thereby suggesting that adjuvant CST does not contribute to the disappearance of radiological lesions.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, our patients were able to leave the hospital after 1 week. In contrast, in historical studies, the time to resolution of fever has exceeded 4 weeks (range, 9-196 days) [4,6,17]; nausea and vomiting has taken 6-8 weeks to resolve [18], and increased levels of liver enzymes persisted for a mean of 4.4 months (range, 1 week to 12 months) [19]. Of note, in our study, CDCrelated radiological abnormalities disappeared within a mean of 106 days (range, 30-210 days)-a result not significantly different from that of historical series (mean, 100 days; range, 28-390 days) [18], thereby suggesting that adjuvant CST does not contribute to the disappearance of radiological lesions.…”
Section: Discussionmentioning
confidence: 71%
“…The studies that have applied PCR methods for patients with hepatosplenic candidiasis are still quite limited [18,20]. Hepatosplenic candidiasis was demonstrated to be a late complication of candidemia among febrile patients with neutropenia, and it was usually noted after the recovery of neutropenia [21,22]. Consequently, if the candidemic phase in these patients is detected early by a sensitive method, such as the PCR assay, Candida infections would be cured quickly by early institution of antifungal treatment, and the occurrence of late complications of hepatosplenic candidiasis would decrease significantly and might even be completely eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this approach include; the importance of the spleen in clearance of particles from the circulation; and, tissue compartmentalization and architecture within the spleen which makes this a convenient organ for dissecting out host specific binding characteristics. The relative importance of the spleen in host defense against disseminated candidiasis is not known, but the incidence of spleen and liver involvement in patients with disseminated candidiasis appears to be increasing 4, 66,67) The importance of mannans in pathogenesis of disseminated candidiasis may be inferred by protection against disseminated candidiasis that is afforded animals who develop an antibody response against the adhesin moieties. In our studies, we found that polyclonal antibody responses against the crude adhesin fraction (2-ME extract) correlated with some degree of protection against disseminated candidiasis.…”
Section: Discussionmentioning
confidence: 99%